Quantifying the response of structural complexity and community composition to environmental change in marine communities. (29th February 2016) - Ferrari, Renata; Bryson, Mitch; Bridge, Tom; Hustache, Julie; Williams, Stefan B.; Byrne, Maria; Figueira, Will
Abstract: Habitat structural complexity is a key factor shaping marine communities. However, accurate methods for quantifying structural complexity underwater are currently lacking. Loss of structural complexity is linked to ecosystem declines in biodiversity and resilience. We developed new methods using underwater stereo‐imagery spanning 4 years (2010–2013) to reconstruct 3D models of coral reef areas and quantified both structural complexity at two spatial resolutions (2.5 and 25 cm) and benthic community composition to characterize changes after an unprecedented thermal anomaly on the west coast of Australia in 2011. Structural complexity increased at both resolutions in quadrats (4 m 2 ) that bleached, but not those that did not bleach. Changes in complexity were driven by species‐specific responses to warming, highlighting the importance of identifying small‐scale dynamics to disentangle ecological responses to disturbance. We demonstrate an effective, repeatable method for quantifying the relationship among community composition, structural complexity and ocean warming, improving predictions of the response of marine ecosystems to environmental change.